THE USE OF MULTIMEDIA TECHNOLOGIES IN LESSONS DURING THE EDUCATIONAL PROCESS AS A PERSPECTIVE OF EDUCATION (Neo Science Peer Reviewed Journal, 2023)
This article discusses the effective methods and importance of using multimedia technologies in the educational process.